Faculty experiences with active student engagement in online doctoral courses during the COVID-19 era: challenges and opportunities—a qualitative study - Welmer, Anna-Karin; Asaba, Eric; Brodin, Nina; Swärdh, Emma (Frontiers in Education, 2025)
ObjectiveDuring the COVID-19 pandemic, universities quickly transitioned from campus-based to online education. However, there is limited insight into how faculty members experienced this transition, particularly in doctoral courses where active student engagement is crucial. This study aimed to explore faculty members’ experiences in promoting active student engagement in online doctoral courses during the COVID-19 pandemic.MethodsA qualitative, inductive approach with a descriptive design was used. Eleven faculty members (3 men and 8 women, median age 51) who served as course leaders in doctoral courses during the pandemic were interviewed. The interviews were recorded, transcribed and analyzed according to reflexive thematic analysis.ResultsThe analysis generated four themes, Facilitating student learning through flexibility and time for reflection, Using social interaction as a catalyst for learning, Enabling student interaction through a safe and structured online environment, and Engaging in digital tools to create variation and engagement.ConclusionOur results suggest that the shift to online education during the pandemic accelerated the development of online doctoral courses, driven by adjustments prioritizing social interaction, self-directed learning, and digital tools. However, challenges such as increased cognitive demands and the added effort required by faculty to foster engagement were also identified.